2013
DOI: 10.5424/sjar/2013114-4220
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the metabolizable energy content of corn for ducks: a comparison of support vector regression with other methods

Abstract: IntroductionCorn (Zea mays L.) is the main energy source in diets for intensively reared avian species (broilers and ducks), therefore accurate information on its effective energy content is of importance to nutritionists. A number of studies have been conducted to estimate the metabolizable energy (ME) content of corn based on its physical characteristics and chemical composition (e.g. Leeson et al., 1993;Zhao et al., 2008). The energy content of feedstuffs depends strongly on their chemical composition. Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, artificial neural network (ANN) had successfully described the drying kinetics of rice (Alam et al, 2018; Beigi, Torki‐Harchegani, & Tohidi, 2017), mosambi peel (Chaurasia, Younis, Qadri, Srivastava, & Osama, 2018) and quince (Taghinezhad, Kaveh, Jahanbakhshi, & Golpour, 2020). However, Faridi, Golian, Mottaghitalab, López, and France (2013) reported that the predictive ability of ANN models showed poor predictive performance on newly introduced data.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, artificial neural network (ANN) had successfully described the drying kinetics of rice (Alam et al, 2018; Beigi, Torki‐Harchegani, & Tohidi, 2017), mosambi peel (Chaurasia, Younis, Qadri, Srivastava, & Osama, 2018) and quince (Taghinezhad, Kaveh, Jahanbakhshi, & Golpour, 2020). However, Faridi, Golian, Mottaghitalab, López, and France (2013) reported that the predictive ability of ANN models showed poor predictive performance on newly introduced data.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, penalised and B-splines models have been used in zero-inflated Poisson models in animal abundance studies (Chiogna and Gaetan 2007), animal models in genetics (Cantet et al 2005), longitudinal nonparametric ANOVA models (Crainiceanu et al 2005) and random regression models in genetic analyses of cattle growth (Meyer 2005). Further, support vector regression was used by Faridi et al (2013) to predict the ME content of corn for ducks and neural network models were used by Faridi et al (2012) to evaluate egg production in response to dietary nutrient intake by hens. Non-parametric models often suffer from the lack of biological interpretation on parameters directly determining the shape of the response curve.…”
Section: Introductionmentioning
confidence: 99%